1996
DOI: 10.1093/carcin/17.7.1395
|View full text |Cite
|
Sign up to set email alerts
|

CANCER BIOLOGY: The human papillomavirus E6/E7 genes induce discordant changes in the expression of cell growth regulatory proteins

Abstract: The E6/E7 oncoproteins of human papillomavirus (HPV) types 16 and 18 are responsible for the efficient immortalization of human genital keratinocytes and we have recently reported that such immortalized cells display alterations in the expression of cyclin A, cyclin B, and cdc-2. To determine whether these alterations were the consequence of E6/E7 protein expression or whether they resulted from the process of cellular immortalization, we multiply-infected primary genital keratinocytes with a retrovirus expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The HK-2 cell line, isolated in 1994 from human renal proximal tubule cells, was immortalized with the human papilloma virus 16 (HPV16) E6 and E7 genes. While studies characterizing the HK-2 cell line have demonstrated their ability to reproduce results seen in isolated proximal tubule cells, the transformation with E6/E7 genes is now known to lead to aberrant cell growth, signaling, and in vitro properties that may not correctly reflect normal proximal tubule cells [26], [28].…”
Section: Discussionmentioning
confidence: 99%
“…The HK-2 cell line, isolated in 1994 from human renal proximal tubule cells, was immortalized with the human papilloma virus 16 (HPV16) E6 and E7 genes. While studies characterizing the HK-2 cell line have demonstrated their ability to reproduce results seen in isolated proximal tubule cells, the transformation with E6/E7 genes is now known to lead to aberrant cell growth, signaling, and in vitro properties that may not correctly reflect normal proximal tubule cells [26], [28].…”
Section: Discussionmentioning
confidence: 99%
“…The HPV integration site in chromosomes varies from case to case, although Cannizzaro and colleagues 57 58 have reported integration at the chromosome 3p fragile site. It is thought that HPV infects epithelial cells and that the viral gene, especially the E6, E7 and E2 products, 59 induces the abrogation of the cell cycle, 46 60 and that in this process squamous metaplasia is induced, and dysplasia and neoplasia develop through further gene alterations. Recently Graham and colleagues 49 have indeed reported that additional genetic alterations in HPV infected cells are thought to be required for the development of a carcinogenic genotype.…”
Section: Discussionmentioning
confidence: 99%
“…The inactivation of Rb, by phosphorylation, mutation, gene deletion or viral oncogenes leads in most cell types to increased proliferation. It also causes overexpression of the di erent cyclins and cdk(s) expressed in late G1 Herrera et al, 1996;Pei, 1996;Tiainen et al, 1996).…”
Section: Discussionmentioning
confidence: 99%